The Encyclopedia of Applied Linguistics 2019
DOI: 10.1002/9781405198431.wbeal0777.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Motivation in Second Language Acquisition

Abstract: Though informed by theories of learning motivation in mainstream psychology, motivation research in second language acquisition has evolved somewhat independently to address the unique social, psychological, behavioral, and cultural complexities of acquiring a new communication code. Founded in the bilingual context of Canada in 1959, second language motivation research originated in a social‐psychological framework implicating attitudes and relations among linguistic communities, as crystallized in the concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…In the conducted research, there was no confirmation of the existence of a connection between students' motivation and the encouragement of their autonomy. Previous research has confirmed the following: if FL teachers succeed in developing students' autonomy and students' language skills, then they will also succeed in influencing student motivation, which contributes to better success in learning a foreign language (Dörnyei & Ushioda, 2011;Little et al, 2003;Liu, 2014;Noels et al, 1999;Ushioda, 2013). On the other hand, previous research confirmed that certain motivational strategies are perceived differently in different cultures.…”
Section: Discussionmentioning
confidence: 87%
“…In the conducted research, there was no confirmation of the existence of a connection between students' motivation and the encouragement of their autonomy. Previous research has confirmed the following: if FL teachers succeed in developing students' autonomy and students' language skills, then they will also succeed in influencing student motivation, which contributes to better success in learning a foreign language (Dörnyei & Ushioda, 2011;Little et al, 2003;Liu, 2014;Noels et al, 1999;Ushioda, 2013). On the other hand, previous research confirmed that certain motivational strategies are perceived differently in different cultures.…”
Section: Discussionmentioning
confidence: 87%
“…Gardner (1985Gardner ( , 2010 a través de sus estudios ha realizado importantes contribuciones al estudio de la motivación en cuanto a su influencia en el proceso de la adquisición de un idioma. Ushioda (2019) define la motivación como una combinación de esfuerzo y deseo del estudiante por aprender una segunda lengua, sólo por el disfrute que le genera esta actividad. Por su parte, Gardner (2005) describe esta variable afectiva como un concepto multifacético, que involucra componentes conductuales, afectivos y cognitivos.…”
Section: Fundamentos Teóricosunclassified
“…El estudio de la motivación en la adquisición de una segunda lengua, se ha caracterizado por investigar perspectivas psicológicas, sociales e individuales-cognitivas sobre la motivación, como una variable independiente que está relacionada con el éxito del aprendizaje de un idioma (Ushioda, 2019).…”
Section: Motivación Para El Aprendizaje Del Inglés Como Segunda Lenguaunclassified